A novel (Tb0.995Ho0.005)3Al5O12 magneto-optical ceramic with high transparency and Verdet constant. (June 2018) - Dai, Jiawei; Pan, Yubai; Xie, Tengfei; Kou, Huamin; Li, Jiang
Abstract: A novel magneto-optical material, (Tb0.995 Ho0.005 )3 Al5 O12 transparent ceramic, was successfully fabricated using co-precipitated powders. The prepared (Tb0.995 Ho0.005 )3 Al5 O12 ceramic exhibits outstanding optical quality and magneto-optical property. For the (Tb0.995 Ho0.005 )3 Al5 O12 ceramic pre-sintered at 1650 °C for 20 h with HIP post-treatment at 1700 °C for 3 h, the optical transmittance exceeds 80% in the 500–1500 nm region (except for the absorption bands). The Verdet constant of the sample at 633 nm is about 1.4 times higher than that of the commercial Tb3 Ga5 O12 single crystal. High transparency and Verdet constant make it an attractive magneto-optical material for the high-power Faraday isolators. Graphical abstract: Unlabelled Image